(untitled) (Palestine Issues on Indonesian Society, 2024)
This paper investigates the role of public demonstrations in mobilizing support for Palestine in Indonesia, focusing on Al-Quds Day rallies as a key mobilizing force. The study explores the history, significance, and political context of these public demonstrations, analyzing how they serve as platforms for political expression and solidarity with Palestine. The paper also examines the broader social and political impact of these protests on Indonesian society, including their role in shaping public opinion, mobilizing grassroots activism, and influencing political discourse. By analyzing Al-Quds Day rallies and other major protests, this paper highlights the role of collective action in promoting Palestine as a central issue within Indonesian political activism. Additionally, the study examines the relationship between these public demonstrations and government policy, exploring the tension between public mobilization and the state’s diplomatic posture.